2021
DOI: 10.47316/cajmhe.2021.2.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D Supplementation in the Prevention of Infection and Severe Course in Covid-19: Testing the Hypothesis

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has disrupted the normal activities of various settings, including clinics, laboratories, and libraries. As the world deals with the fast-mutating causative virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), apart from the search for the best vaccine candidate, efforts towards repurposing existing molecules to save lives must continue. Considerable interest has centered around the implications of vitamin D deficiency and its supplementation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies have found lower levels of vitamin D to be linked to a higher risk of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), as well as severe coronavirus disease 2019 (COVID-19) and increased risk of hospitalization [26,27,28]. Interventional studies have also found vitamin D supplementation to be associated with faster recovery and reduced risk of worsening in those with COVID-19 [29,30].…”
Section: Covid-19 Vitamin D and Agementioning
confidence: 99%
“…Studies have found lower levels of vitamin D to be linked to a higher risk of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), as well as severe coronavirus disease 2019 (COVID-19) and increased risk of hospitalization [26,27,28]. Interventional studies have also found vitamin D supplementation to be associated with faster recovery and reduced risk of worsening in those with COVID-19 [29,30].…”
Section: Covid-19 Vitamin D and Agementioning
confidence: 99%